2012
DOI: 10.1017/s003118201200100x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of host ecology and biogeography on the helminth species richness of freshwater fishes in Mexico

Abstract: Freshwater fish helminths, the most well known Mexican vertebrate parasites, include approximately 260 species (platyhelminthes, acanthocephalans, nematodes, and hirudineans). The distribution patterns of adult helminth diversity (throughout parasite and host groups and hydrological regions) are described and the effects of host traits and environmental and geographical factors on diversity are evaluated. Adult helminths include 160 species, parasitizing 149 fish species of 23 families distributed in 21 region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 67 publications
1
6
0
2
Order By: Relevance
“…The size of the available pool of parasite species between the neotropical and the nearctic regions must be different; this being a constraint on the number of parasite species a fish host can acquire over time. The results and interpretations in this study are also supported by a previous study that used species richness to describe the distribution patterns of adult helminth diversity [30].…”
Section: Discussionsupporting
confidence: 87%
“…The size of the available pool of parasite species between the neotropical and the nearctic regions must be different; this being a constraint on the number of parasite species a fish host can acquire over time. The results and interpretations in this study are also supported by a previous study that used species richness to describe the distribution patterns of adult helminth diversity [30].…”
Section: Discussionsupporting
confidence: 87%
“…Culumber et al (2011) reported that X. malinche is confined to fewer localities in the Pánuco drainage than X. birchmanni. Thus, according to the hypotheses of Garrido-Olvera et al (2012), the difference in the distribution of these 2 species of fish is an important factor contributing to the differences in the structure of their helminth communities.…”
Section: Discussionmentioning
confidence: 99%
“…2012), whereas host diet could have a stronger influence for endoparasites than phylogeny, due to the trophic transmission of endoparasites (see Garrido-Olvera et al . 2012). Future studies that include information of the phylogenetic, biological and ecological characteristics of host species may clarify which factors are most important to build up the modular structure of host–parasite networks.…”
Section: Discussionmentioning
confidence: 99%